The High Cost of Low Wages: Does Maquiladora Compensation Reduce Turnover? - Miller, Janice S.; Hom, Peter W.; Gomez-mejia, Luis R. (Journal of International Business Studies, 2001)
We determined which compensation practices of American-owned plants in Mexico reduced turnover. Regression revealed that profit-sharing and saving plans lowered turnover, while most pay forms did not. We discussed these findings within a national culture approach to compensation administration.